Análise do nível de maturidade da gestão do conhecimento na criminalística federal - Mendes, Raphael Borges (2013)
Knowledge management represents a new responsibility for the public administration to let it grow its services effectiveness and better the society that it serves, in that helps organizations dealing new challenges, deploy innovating practices of management and enhance the quality os process, products and public services. Whereas the knowledge management’s process embraces five steps represented by identifying, creating, storing, sharing and utilizating the organizational knowledge, a first mapping of the KM practices already existing at the National Criminalistics Institute is very important. As a new practice in brazilian public organizations, many evaluation methods were found in the scientific literature. Therefore, the IPEA method was chosen, as the National Criminalistics Institute has not already started an institutional initiative to implement KM practices. By the way, the survey results revealed that the National Criminalistics Institute is in an early stage of KM development, when the organization recognizes the significance and the requirement of managing the knowledge originated in the circunstances os its activities. Furthermore, specific actions related to codifying organizational informations and knowledges were found scattered.